Effect of calcitonin gene-related peptide-induced preconditioning on attenuated endothelium-dependent vasorelaxation induced by lysophosphatidylcholine - Tang Yu-Hai; Lu Rong; Li Yuan-Jian; Peng Chang-Fu; Deng Han-Wu (Acta Pharmacologica Sinica; Vol 18, No 5 (September 1997): Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of calcitonin gene-related peptide (CGRP)-induced preconditioning on the inhibition of endothelium-dependent vasorelaxation to acetylcholine (ACh) by lysophosphatidylcholine (Lys) in the isolated rabbit and rat thoracic aortas. METHODS: Endothelium-dependent relaxation to ACh was studied in the aortic rings precontracted with phenylephrine 0.1 mumol.L-1 in the absence or presence of Lys. RESULTS: On the rabbit aortic rings, Lys 5 mg.L-1 impaired vasodilator responses to ACh. Pretreatment with CGRP 0.1 mumol.L-1 for 5 min attenuated the inhibition of vasodilator responses to ACh by Lys. The effect of CGRP was blocked by 1-(5-isoquinolinysulfonyl)-2-methylpiperazine (H-7), an inhibitor of protein kinase C (PKC) (% relaxations to ACh 1 mumol.L-1 were 88 +/- 4, 28 +/- 10, 65 +/- 13, and 25 +/- 10 for control, Lys, Lys + CGRP, and Lys + CGRP + H-7, respectively). The same effects of CGRP were shown in the rat aortic rings, and the effect of CGRP was also abolished by H-7 (% relaxations to ACh 1 mumol.L-1 was 84 +/- 10, 55 +/- 11, 76 +/- 11, and 50 +/- 14 for control, Lys, Lys + CGRP, and Lys + CGRP + H-7, respectively). CONCLUSION: CGRP-induced preconditioning protected the endothelium against injury elicited by Lys, the effect of CGRP is related to the activation of PKC.